The concept of professional judgment of accountant: concept, essence and content - Shylmaganbetova, D.А.; Janshanlo, R.Е.; Berdikhojayeva, M.S. (BUKETOV BUSINESS REVIEW, 2024)
Object: The study aims to consider one of the accounting tools — the professional judgment of an accountant and to generate the most suitable definition from the point of the authors` view for this economic category. Methods: The studies have used comparative, logical analysis, typology and grouping, methods of induction and deduction. To ensure the reliability of the study, the literature review utilized the works of various renowned authors on accounting. The comparison of various findings of different studies were scrutinized and based on the analysis of professional judgment resources, a definition of the phenomenon was proposed. IFRSs, which require professional judgment of an accountant, have also been studied and the rationale for the study of the essence of this economic category has been provided. Findings: Various approaches of authors related to the concept and classification of accountant's professional judgment were analyzed, and the author's definition of this economic category was formed. The question of the place and role of professional judgment as one of the accounting tools in the accounting system is considered. Justifications are given about its use for measuring accounting objects, reflecting the facts of economic activity of subjects and pre senting financial information to users for correct decision making within the framework of the current accounting standards. The need to analyze the accountant's professional judgment as the main category of accounting theory and develop the concept of professional judgment was justified. Conclusions: Professional judgment of the accountant is one of the important economic categories of accounting, which in the current realities plays an important role in the preparation of financial statements of the company and its disclosure, which depends on education, special knowledge of the specialty, experience and other personal characteristics, also on the information on the situation to be solved.